Management of bilateral Eagle's syndrome with pharmacotherapy: a case report - Garg Ranjana; Veerabhadrappa Suresh Kandagal; Gupta Vivek Vijay; Yadav Seema (Journal of Oral Medicine and Oral Surgery)
Eagle's syndrome is a frequently overlooked nosological condition that arises from an elongated styloid process or calcified stylohyoid ligament, resulting in varying degrees of cervicofacial or craniofacial pain. Diagnosis typically relies on a physical examination of the styloid process in the tonsillar fossa, which exacerbates pain during neck movements. Radiographic evaluation should encompass orthopantomography (OPG) and Cone Beam Computed Tomography (CBCT), revealing styloid elongation exceeding 3 cm. While surgical reduction of the styloid process via intraoral or external approaches remains the cornerstone, some patients benefit from pharmacological interventions. Here, we elucidate the case of a 37-year-old woman experiencing cervicofacial pain exacerbated by neck movements, opting for conservative therapy with gabapentin, amitriptyline, and paracetamol. Her symptoms markedly improved over a three-month follow-up period.